(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Development Communication is described as the systematic use of communication in support of national development. The individuals who conceived development communication/ journalism in 1960s believed that there should be better trained and informed economic specialists among the communicators. The growth in the Third World is characterized by structural inequalities and cleavages. The income gap between rich and the poor is becoming wider. As a consequence, the economic growth only contributes to the problem of growing disparities, tendencies towards disintegration and instability.Development Journalism is the need of the hour. By concentrating on the development landmark the news agencies can help Third World countries tackle their problems of economic and social development, national unity and stability and culture preservation.The remedy neither lies in measures to restrict and control the dissenting voices nor by strengthening their down capacity to communicate by attempts to block or tear down the capacities of others. A single standard of control of communication systems throughout the world will certainly prove counterproductive. For the worldwide need is for more voices and not fewer.